Content of Heavy Metals in the Soils of the Aragats Mountain Range - Hunanyan, S. A.; Jhangiryan, T. A.; Mkrtchyan, A. L. (ՀԱԱՀ հիմնադրամ)
The article considers the content and distribution patterns of heavy metals in the soils of the Aragats mountain range. The presence of heavy metals in various types of soils and migration along the soil horizons have been established based on the results of the research study. According to the content of soils, heavy metals are arranged in the following row: Zn>Cu>Pb>Co>Mo>Cd. The content of gross and mobile forms of heavy metals in the soils varies unevenly from top to down depending on the nature of the metals. The correlation link between the content of humus, reaction of the environment, mechanical composition of soils, gross forms of nutrients and the content of metal forms (r=0.63±0.015 - 0.73±0.011) has been revealed.
Keywords: Agronomy and Agroecology